Athletic career transition in former Chinese elite athletes: An empirical investigation and cross-cultural comparison with findings from Germany - Huang, Z. (2002)
The effects of competitive sport participation on the life-span development of elite athletes are receiving increasing amounts of research interests. An action theory framework is proposed in the present study (a) to integrate various theoretical approaches that are applied in the studies in this field, (b) to interpret the influences of different cultural backgrounds and sport system on the athletic career development and career transition process in former athletes from Germany and China, (c) to provide a methodological background for the quantitative and qualitative measurements used in the present study. An in-depth investigation was held in China in 1998. 350 covered questionnaires with simple introduction were delivered via post to former athletes in China. 149 (42.6%) valid answers are returned at the deadline. 28 individual interviews were carried out with the volunteers in the 149 final participants. All the quantitative and qualitative empirical results were analyzed and interpreted from an action theory perspective and compared with the empirical findings of a previous study conducted in Germany in 1997. Interesting differences and commonalities were detected with regard to the quantitative and qualitative data. Other than isolated cases, most interviewed athletes reported that they were rather satisfied with athletic careers. Differences in educational and occupational aspects were found between the two country (cultural) groups. Due to a close relationship and co-operation between universities and the sport system, more former Chinese elite athletes achieved an academic degree, mostly with a strong connection to sport. Further qualitative comparisons between the interviews provided a comprehensive description and understanding of the athletic career processes. Characteristics of the actors (elite athletes as intentional subjects developed in different social cultural backgrounds and sport systems), the task (athletic career transition, postathletic career development in different value systems, norms etc.) and the environment (social-cultural and institutional characteristics of the competitive sport system) were considered. The results of the present study provided a meaningful theoretical perspective for the elaboration of an action theory based sport specific transition concept including life development intervention aspects (career counselling and environmental management). The action theory perspective has been proved to have unique advantages in the study of life-span career development process, the interpretation of social cultural influences on actions, as well as the methodological issues in both fields. A comprehensive understanding of athletic career transition and post-athletic career development process in different sport systems will be useful in the development and implementation of future career assistance programs.